Purification of The Lipase B of Candida antarctica from a Commercial Enzymatic Extract - Llerena Suster, Carlos Rafael (2014)
This paper presents a rational strategy to purify the lipase B of Candida antarctica of the commercial extract Lipozyme® through size exclusion coupled with anionic exchange chromatography using a non conventional, easy to remove buffer system such as ammonia-ammonium. In this context, each step of the purification was followed through the determination of the protein content, esterase activity measurements, SDS-PAGE, agarose electrophoresis, UVspectroscopy and isoelectric focusing. The purification of the commercial extract afforded a sample that retains 47% of the proteins (being CALB the major enzymatic component of the purified sample) with a hydrolytic activity higher than the starting crude extract.